Identification of the chemical profile and evaluation of the antimicrobial effect of Eryngium billardieri Delar essential oil component against bacterial species of agricultural and food interest - Hajian-Maleki, Habibeh; Shams-bakhsh, Masoud (Frontiers in Microbiology, 2023)
The studies on the antibacterial activity of the essential oil of E. billardieri are almost blank.Herein, we have diagnosed this herb as a natural complex effective against several bacteria which was examined by disk diffusion and broth microdilution susceptibility methods. Primary estimation of the antimicrobial effect of this herbal compound by disk diffusion showed that the oil could inhibit the growth of tested bacteria by appearance of the haloes between 8.25-21.25 mm. In the next step, Tthe oil was found to be active against all 24 tested Gram-negative and Gram-positive bacteria in the broth media, at minimum inhibitory concentrations ranging from 0.67 to 34.17 g L -1 and Enterococcus faecalis and Curtobacterium flaccumfaciens pv.flaccumfaciens were the most sensitive food and plant pathogenic bacteria, respectively. The GC-MS (Gas chromatography-mass spectrometry) analysis was employed to assign the ingredients present in the oil and thirty-four different components representing 95.71 % of the total oil were identified, with n-Hexadecanoic acid being the dominant, followed by 2-Pentadecanone, 6,10,14-trimethyl, 2-Pentadecanone, 6,10,14-trimethyl, 1H-Indene, 1ethylideneoctahydro-and Cinnamyl tiglate. These findings demonstrate, for the first time, a broad spectrum of antibacterial capacity for E. billardieri and based on these observations, it